DOZ047.120: The role of proton-pump inhibitors in eosinophilic esophagitis: focus on esophageal atresia children. (24th June 2019) - Tambucci, R; Rea, F; Malamisura, M; Torroni, F; Romeo, E F; Faraci, S; Angelino, G; di Abriola, G F; Guerra, L; Caldaro, T; Contini, A C I; Balassone, V; et al.
Abstract: Introduction: Since recently, after detection of eosinophilic predominant inflammation of esophagus a trial with proton-pump inhibitors (PPIs) was needed to individuate children with PPI-responsive esophageal eosinophilia (PPI-REE), only those non-responders received eosinophilic esophagitis (EoE) diagnosis. In 2018 updated international consensus suggested removing the PPI trial as a diagnostic criterion and consider PPIs as a treatment together with diets and topical steroids. The role of PPIs is evaluated in children with esophageal atresia (EA) and EoE versus EoE from general population. Method: A retrospective chart review of both children with EA and EoE followed-up from at January 2005 has been performed. According to ESPGHAN guidelines published in 2014 patients showing eosinophilic inflammation received high-dose PPI trial to identified PPI-REE. Those non-responders were labeled as EoE and underwent to dietary and/or topical steroid treatment. Demographics and disease characteristics of EA patients with EoE were analyzed and compared with those with EoE from general population. Results: Overall, 370 EA and 118 EoE patients were analyzed. Of them 15 EA-EoE patients were detected. Consequently, in our cohorts, 4.0% of EA patients developed EoE. Male-to-female prevalence ratio was of 2.55 with no difference in gender prevalence between groups. At diagnosis EoE-EA children were significantly younger compared to EoE group (mean: 5.1 vs 10.8 years; P < 0.0001). Peak EOS/HPF at diagnosis did not differ between groups (50.1 ± 26 vs 59.8 ± 29 EOS/HPF). No difference was observed in allergy prevalence between groups (53.8 vs 68.0%). PPI-REE was significantly more prevalent in EA-EoE group that in EoE group (66.6% vs 19.4%; P = 0.0004). Conclusion: Similar gender distribution and high prevalence of allergy suggest that common genetic susceptibility factors for EoE exist. However, high prevalence of PPI-REE coupled early EoE onset might also suggest that other factors (e.g. esophageal motility disorders) might play a physiopathological role in EoE development in EA children. Our study suggests that a stepwise approach with PPIs as a first-line treatment for EoE management in EA children should still be considered.